Gambaran Risiko Kejadian Carpal Tunnel Syndrome pada Karyawan Administrasi Universitas Kristen Krida Wacana - Suparto Suparto; Vanessa Malise Lisandra; Irvan Tanpomas; Citra Rencana Perangin-angin (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2020)
Carpal Tunnel Syndrome (CTS) is a neurological disorder on upper extremities in which the medianus nerve is impinged. Carpal tunnel entrapment can be caused by multiple causes. One of the most common cause is job-related activities of repeated flexion and extension of wrist such as in typing activity. This study aimed to describe the incidence of CTS in university administrative employees. This was a cross-sectional study conducted at Krida Wacana University in 2019. Twenty-nine respondents were included in the study by a purposive sampling. Subjects filled out questionnaires describing troubling symptoms, age, gender, typing duration per day, work period, wrist position, and Phalen’s test to assess CTS incidence. Data were analysed with SPSS 23 software. Incidence risk for CTS was found in respondents from various age groups (40-60 years old), with 11 (37.9%) respondents were CTS-risk, and 16 respondents were CTS-positive. Eighteen respondents with typing duration of > 4 hours/day was found to be at risk for CTS. Of respondents group with odd wrist position, 16 (55.2%) of them were at risk to suffer CTS. The study concludes that the incidence of CTS in administrative employee increases with advancing age, working duration, and awkward hand position while working. Thus, education is required for the administrative employees about factors causing CTS risks.